Stress Intensity Factor For Cracks In Bonded Dissimilar Materials - K B Hamzah; N M A NikLong; N Senu; Z K Eshkuvatov (IOP Publishing Ltd, 2024)
In this paper, an inclined and a semi circular arc cracks lying in the upper half of bonded dissimilar materials are considered.The modified complex variable function method is used to formulate the problem into the hypersingular integral equations (HSIEs) with the help of the continuity conditions of the traction and displacement.The traction along the crack serves as the right hand side of the integral equation. The HSIEs is solved numerically for the unknown crack opening displacement function using the appropriate quadrature formulas. Numerical results presented the behaviour of the nondimensional stress intensity factorsat the crack tips which are depends on the elastic constants ratio, the position of the crack and the distance between the crack and the boundary.